Pengungkapan Sustainability Report Terhadap Harga Saham - Mitha Amalia Sofiatun; Maria Goretti Kentris Indarti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study examines the effect of sustainability report disclosure on the stock prices of companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. Sustainability reports consist of economic, environmental, and social performance data. A total of 252 observations from 77 companies were collected using purposive sampling. Multiple linear regression analysis was performed, controlling for company size, profitability, and leverage. The results indicate that economic performance significantly positively affects stock prices, while environmental and social performance do not affect them.